EVOLUTIONARY EFFECTS IN CLOSE BINARIES: ANALYSIS OF THE DISTRIBUTION OF ORBITAL ECCENTRICITIES - Cherepashchuk, A. M.; Karetnikov, V. G. (Одеські астрономічні публікації, 2017)
Dependencies of orbital eccentricity e on orbital periods P in close binary systems (CBS) of different masses and ages, being at the Main Sequence (DMS) and being eclipsing binary stars (EBS), are reviewed. The EBS groups of similar age are separated into objects with convective (A-M - stars) and radiative (O-B - stars) envelopes, and into the group of massive stars. It has been found, that the value of 6 always increases with increasing P and decreases with relative radius of the main star of EBS. In all groups of stars, the transition period P tr ~ 3d : for P < 3d, e=O, for P > 3d, e ≠ 0. As for the majority of semi-detached stars (SDS), P < 2d, it is possible to assume, that the circularization of their orbits took place at the DMS stage. The comparison of dependencies of orbital eccentricities on orbital periods in EBS and WR+O systems has shown distinction in the values of P tr (3d and 14d, respectively, that specifies difference in mechanisms of orbital circularization in these types of binary stars.